Event-triggered control co-design for rational systems⁎This study was financed in part by the Coordenação de Aper-feiçoamento de Pessoal de Nivel Superior - Brazil (CAPES) - Finance Code 001 (PROEX, SticAmSud 88881.143275/2017-01); CNPq, Brazil (grants PQ 307449/2019-0, Univ-422992/2016-0 and PQ-302690/2018-2); IFSUL, Brazil (Project PD00190519/011); STIC AMSuD 18-STIC-01, CoDysco2 - France; ANR project HANDY 18-CE40-0010. Issue 2 (2020) - Moreira, L.G.; da Silva, J. M. Gomes; Coutinho, D.; Tarbouriech, S.
Abstract: This work deals with the problem of designing stabilizing event-triggered state-feedback controllers for rational systems. Using differential algebraic representations and Lyapunov theory techniques, LMI-based conditions are derived to ensure regional asymptotic stability of the origin. These conditions are then cast into a convex optimization problem to the co-design of the event generator parameters and the state-feedback gain in order to reduce the controller updates while ensuring the asymptotic stability of the origin with respect to a given set of admissible initial conditions. The proposed methodology is illustrated by means of a numerical example.